TOOTH FRAGMENT REATTACHMENT OF COMPLICATED CROWN FRACTURE WITH 1 YEAR FOLLOW UP: A CASE REPORT - JACOB, DR. JERRIN; VENKATESH, DR. ALAGARSAMY; TAMILSELVI, DR. R.; PARTHASARATHY, DR. REVATHY; S, DEVADHARSHINI (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Aim & Background: This report presents the conservative management of a complicated crown fracture. Among various treatment options, reattaching a crown fragment is a viable conservative approach for anterior tooth fractures. In a remarkable display of modern dentistry, a fractured tooth was skilfully redeemed through the innovative reattachment of its fragmented crown, expertly secured with a glass fiber post, showcasing a harmonious blend of art and science in restorative dental care. Case Description A female patient, aged 32, was treated for traumatic injuries sustained in an accident, which resulted in crown fractures of her upper central incisors, specifically affecting the right and left maxillary teeth. The fracture in tooth 11 was oblique, extending from the buccal to the palatal aspect, extended sub gingivally on the mesiopalatal area involving enamel, dentin and pulp and Ellis class 2 fracture in 21. Root canal treatment was performed promptly. Crown-lengthening procedure was performed to expose the fracture line. The fragment was reattached using fibre post with dual cure resin cement. At the 1-year follow-up, the tooth demonstrated excellent functional and esthetic outcomes, with the patient experiencing no adverse issues. Conclusion: Due to the recent advancements in the dental materials and implication of appropriate technique, esthetic outcomes are foreseeable. Therefore, reattaching a tooth fragment is an alternative method for restoring both function and aesthetics using an extremely conservative approach. Clinical significance :Reattaching fractured tooth fragments is a practical restorative option for dentists, as it effectively restores dental functionality and aesthetics while being highly conservative and cost-effective.